ERRATARIUM for Real-Time Systems - Nelissen, Geoffrey (2017)
Hundreds of papers published each year • Some of them inevitably contain mistakes, errors, typos, … • All errors, big or small, deserve to be known by everyone • To avoid their spread in other works • To avoid teaching wrong results • To allow people to find appropriate solutions • To learn from them and not reproduce them later